Pengaruh Pemberian Kompensasi Terhadap Prestasi Karyawan: (Studi pada PT Telekomunikasi Indonesia.Tbk. Cabang Langkat) - Safina, Wan Dian; Wirananda, Henny Andriyani (Al-Buhuts, 2023)
Competence of human resources in this study through communication and group collaboration factors that affect the effectiveness of employees at PT. Telkom Indonesia Regional I Sumatra. The data analysis technique used is descriptive and quantitative analysis. The results showed that the Communication and Group Cooperation which had an influence on Employee Work Effectiveness by 77.0% were categorized as very strong. So it can be denied that in measuring the competence of human resources through communication and group factors has a positive and significant influence in supporting the work strength of employees in the company.